Люминесцентные свойства и морфология композитных материалов ZNWO 4; Известия вузов. Физика; Т. 57, № 12/3 - Валиев Д. Т. Дамир Талгатович; Полисадова Е. Ф. Елена Фёдоровна; Тупицына И. А. Ирина Аркадьевна; Жоров А. А. Анатолий Александрович (2014, 2014)
Заглавие с экрана